Qur’ānic approach to peace building: action guide from the mother and the sister of prophet Mūsā - Bahari, Che Amnah (IIUM, 2020)
Peace building refers to a process of establishing peace and preventing the recurrence of violence by addressing the root cause and effect of the conflict through constructive understanding and reconciliation. Al-Qur’ān in many circumstances has highlighted the term iṣlāḥ, which means peace as opposed to war in everyday life, in the form of action guides of the people of the past. This paper attempts to study the Qur’ānic approach to peace building by studying the term iṣlāḥ and other related terms from various Qur’ānic verses in connection with the vicious events confronted by the mother and sister of Prophet Mūsā and the good-natured actions applied by them to overcome the mishaps. This article concludes that utilizing Islamic, universal values and principles will increase the possibility for peaceful change and development in community, which is conducive to harmonious and peaceful co-existence.